Profile of Infant Feeding Practices, Household Socioeconomic Conditions, and Food Access Among Stunted children under five in Disaster-Prone Areas of West Aceh - Iken Rahma Mahesty; Ranita Suri Dewi; Laila Apriani Hasanah Harahap (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2026)
Background: Stunting is a global health problem that occurs frequently in developing countries, especially in low- to middle-income countries. In addition, disaster-prone areas such as West Aceh have a high risk of food insecurity, which can be a contributing factor to stunting. The prevalence of stunting in Aceh (28.6%) is higher than the national figure (24.4%). Objective: The purpose of this study was to describe feeding practices, exclusive breastfeeding, social and economic status, food access, and the lack of nutritional education among mothers of stunted children under 5. Method: This study used a descriptive cross-sectional analysis and was conducted in Woyla District, West Aceh in February 2026. The subjects of this study were 30 mothers of stunted childern who were given questionnaires and 24-hour recalls of their children's intake. Results: 56.7% of stunted childern received exclusive breastfeeding and only 36.3% of stunted childern received appropriate feeding. In addition, the level of parental education (60%) and family income (70%) of stunted children were relatively low. The research also showed inadequate access to food and the lack of nutrition education for families of stunted toddlers. Conclusion: Stunted childern in Woyla District, West Aceh, still require appropriate treatment due to numerous contributing factors that have not been addressed, such as inappropriate feeding practices, low education and income, difficult food access, and the lack of nutrition education for families.Keywords: Stunted, Children under five, Disaster Prone Areas, Infant Feeding, Socioeconomic Conditions